Effect of orchard floor management treatments on soil hydrothermal regimes under rainfed conditions of Himachal Pradesh in nectarine (Prunus persica var. nucipersica) cv. Snow Queen - SHARMA, SUMEET; SHARMA, D P (The Indian Journal of Agricultural Sciences, 2018)
The present investigation was carried out to study the effect of orchard floor management treatments on soil hydrothermal regimes under rainfed conditions of Himachal Pradesh in nectarine cv. Snow Queen during the years 2016 and 2017. The experiment was laid out in a Randomized Block Design replicated four times. The experiment consisted of seven treatments including control. Among these treatments, soil hydrothermal regimes were maintained effectively under black polythene mulch. Bicolour polythene mulch recorded maximum fruit size (length- 52.85, 57.27mm; breadth- 51.21, 55.04 mm), fruit weight (77.86, 89.41 mm), proportion of â€œAâ€ grade fruits (62.15, 66.48 %), whereas maximum fruit yield (42.44, 54.63 kg/tree and 16.98, 21.85 tonne/ha) was recorded under black polythene mulch in 2016 and 2017, respectively. However, the minimum values of hydrothermal regimes, fruit size, fruit weight, proportion of â€œAâ€ grade fruits and fruit yield were recorded under control during both the years of the study.